1992
DOI: 10.1002/1097-0142(19920801)70:3<704::aid-cncr2820700327>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive combination chemotherapy for regionally advanced unresectable extramammary Paget carcinoma

Abstract: Extramammary Paget carcinoma (EPC) is considered to originate from the eccrine and apocrine glands of the adnexal skin of the axilla, vulva or penis, scrotum, or perineum. If immunohistochemical techniques with the use of cytoskeletal markers are applied in addition to histologic examination, EPC lesions are found to be multifocal adenocarcinoma of the adnexal sweat glands. So far, therapeutic approaches have included primary surgery, followed optionally by radiation therapy. It is possible to achieve a cure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Various chemotherapeutic agents have been used, but no standardized regimen currently exists. Some investigators have presented case reports documenting the effective treatment of primary, recurrent, or metastatic tumors of EMPD with cisplatin, carboplatin, 5-fluorouracil, vincristine, bleomycin, mitomycin C, etoposide, or docetaxel, either alone or combined (3,4,(31)(32)(33). However, almost all the follow-up periods were #2 years, and the effects of chemotherapy on the prognosis of EMPD patients are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Various chemotherapeutic agents have been used, but no standardized regimen currently exists. Some investigators have presented case reports documenting the effective treatment of primary, recurrent, or metastatic tumors of EMPD with cisplatin, carboplatin, 5-fluorouracil, vincristine, bleomycin, mitomycin C, etoposide, or docetaxel, either alone or combined (3,4,(31)(32)(33). However, almost all the follow-up periods were #2 years, and the effects of chemotherapy on the prognosis of EMPD patients are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Balducci et al (13) reported a CR in a patient with extramammary Paget's disease with continuous 5‐FU administration combined with MMC. Voigt et al (3) reported a CR in a similar patient using carboplatin, 5‐FU, and calcium folinate. These regimens used standard chemotherapy doses approved for other gynecological malignancies in young patients.…”
Section: Discussionmentioning
confidence: 97%
“…Invasive genitourinary tract cancers (prostate, bladder, kidney) [22][23][24][25][26][27][28] or gastrointestinal sites (colon, rectum, liver) 29,30 can be associated, synchronously or metachronously, with penoscrotal empd, but the frequency of this association is not consistently reported. In a recent M.D.…”
Section: Discussionmentioning
confidence: 99%